La discapacidad auditiva y su incidencia en el proceso de enseñanza y aprendizaje en básica elemental de la escuela “Lic. Jaime Andrade Fabara”, en el año lectivo 2021-2022 - Mena Ayala, Vanessa Margoth (2022)
The present investigative work allows us to help children with hearing disabilities through a guide of playful activities that allow them to develop skills and abilities, the objective of the research is to strengthen the teaching and learning process of students with hearing disabilities. in the Lic. Jaime Andrade Fabara school, including them with all the students and not only with the students with Special Educational Needs (SEN) of the school community in the school. The methodology used in the research is a descriptive and qualitative approach supported by bibliographic research, through which the theoretical and conceptual foundations referring to the Special Educational Needs (SEN) of students with disabilities, specifically with hearing disabilities, have been abstracted. at school; The investigation was in field in which research techniques and instruments were used, such as: interview with the director and surveys to the teachers and observation sheets for students of the basic general school "Lic. Jaime Andrade Fabara. In the present investigation it was evidenced that the lack of teacher training limited the learning of students with SEN, who were unaware of techniques and strategies to reach students with disabilities, with the development and application of the research project it was possible to train in basic sign language to the teaching staff of the school, benefiting students with special educational needs associated with a hearing disability. The results obtained improved the teaching and learning process using innovative dynamics, recreational activities in which all boys and girls were integrated.